Entry Denied: COVID-19, Race, Migration, and Global Health - Sirleaf, Matiangai (Frontiers in Human Dynamics, 2020)
This essay uses the novel coronavirus pandemic as an entry point to explore the intersections between race, migration, and global health. The pandemic is simultaneously reviving stereotypical colonial imaginations about disease directionality, but also challenging racialized hierarchies of diseases. This essay illuminates how the racialization of diseases is reflected in historic and ongoing United States’ migration law and policy as well as the global health law regime. By demonstrating the close relationship between often separately treated areas, the essay clarifies underlying currents in global health and migration law and policy that stem from fears of the racialized other. Rendering these intersections visible creates avenues for rethinking and reshaping both theory and praxis toward anti-subordination efforts.